Belgian Modern Art : An Selection by Veranneman Foundation. - Liebaers, Herman; Stichting Veranneman, Kruishoutem (Tokyo : Yurakucho Art Forum, 1988)
Ensor, James ; Permeke, Constant ; Delvaux, Paul ; Magritte, René ; Mara, Pol ; Raveel, Roger ; Bogart, Bram ; Landuyt, Oscar ; Wyckaert, Maurice ; Alechinsky, Pierre ; Nellens, Roger ; Moeschal, Jacques ; Gentils, Vic ; D'Haese, Roel ; Reinhoud
Belgian Modern Art : An Selection by Veranneman Foundation, Yurakucho Art Forum, Tokyo, 1988.11.13 - 11.13
English-Japanese
kunstcatalogus
Keywords: België